Slack and innovation: The role of human resources in nonprofits. Issue 2 (7th June 2018) - Meyer, Michael; Leitner, Johannes
Abstract : Resources are often seen as a key factor in innovation. For business organizations, it has been shown that there is a relation between the lack or abundance of resources and the innovativeness of organizations. It is specifically abundance that fosters innovations, not shortage. We investigated this relationship for nonprofits based on a cross‐sectional survey of 250 Austrian nonprofit organizations (NPOs). According to levels of disposability, we differentiate between available slack, recoverable slack, and potential slack. Turning to the type of resources, we distinguish financial slack from different types of HR slack: levels of motivation and qualification and levels of compensation, addressing the level of employees' wages. Our results indicate that in NPOs human resources slack rather than financial slack has a positive impact on innovativeness.